Building Information Modelling (BIM) Standardisation for Optimal Urban Infrastructure Asset Management (AM) - Mohd Nor, Nurul Nasuha; Mohd, Norhazren Izatie (Research in Management of Technology and Business, 2025)
Building Information Modelling (BIM) has emerged as a revolutionary technology in architecture, engineering, and construction (AEC). It facilitates the creation and management of digital representations of physical and functional characteristics of built environments. BIM has transformed traditional approaches to project design, construction, and maintenance by enabling multi-disciplinary collaboration and fostering efficient decision-making. Particularly in urban infrastructure, which involves complex networks of interconnected systems, BIM offers unparalleled potential for streamlining workflows and optimising resource utilisation. However, the actual value of BIM extends beyond the construction phase; it plays a pivotal role in Asset Management (AM). This involves managing the life cycle of assets, from handover to operation and maintenance, where the quality and structure of BIM data are critical. Despite its immense promise, the integration of BIM into AM has faced challenges, mainly due to inconsistencies in data classification and the lack of standardisation across projects. These issues hinder the effective use of BIM in AM and highlight the pressing need for a standardised information and parameter management framework.